The Diffusion of the Internet : A Cross-Country Analysis - Andres, Luis; Cuberes, David; Diouf, Mame; Serebrisky, Tomas (2012)
This paper analyzes the process of Internet diffusion across the world using a panel of 214 countries during the period 1990-2004. Countries are classified as low- or high-income and it is shown that the diffusion process is characterized by a different S-shaped curve in each group. The estimated diffusion curves provide evidence of very slow "catching up". The paper also explores the determinants of Internet diffusion and shows that network effects are crucial to explain this process. One important finding is that the degree of competition in the provision of the Internet contributes positively to its diffusion.